Adjuvant Therapy Trials. Issue 3 (May 2016) - Ursem, Carling; Van Loon, Katherine; Venook, Alan
Abstract : Abstract: In 2015, ramucirumab and TAS-102 became the 10th and 11th drugs approved by the Food and Drug administration for the treatment of patients with colorectal cancer, not counting leucovorin, and yet only 3 agents, 5-fluorouracil, capecitabine, and oxaliplatin, have proven benefit in adjuvant treatment. In fact, there have been no additions (and 1 subtraction levamisole) to our arsenal of therapies for patients with stages II and III colon cancer for more than a decade. How did we get here? Are we stuck? And how do we move forward?